2016
DOI: 10.3390/nano6010018
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Banana Peel–Derived Porous Carbon Foam as Binder-Free Electrode for Supercapacitors

Abstract: Nitrogen-doped banana peel–derived porous carbon foam (N-BPPCF) successfully prepared from banana peels is used as a binder-free electrode for supercapacitors. The N-BPPCF exhibits superior performance including high specific surface areas of 1357.6 m2/g, large pore volume of 0.77 cm3/g, suitable mesopore size distributions around 3.9 nm, and super hydrophilicity with nitrogen-containing functional groups. It can easily be brought into contact with an electrolyte to facilitate electron and ion diffusion. A com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Hence, it can be concluded that the binder content should be reduced to a minimum or that binder should even be avoided in electrode manufacturing. Liu et al already made first attempts to develop such binder-free electrodes based on banana peel (Liu et al, 2016), but this approach is relatively new and far from being able to be implemented in electrode production on an industrial scale. The higher EC values of AC-600-800-add compared to those of AC-add can be explained by the lower surface are of the commercial AC in comparison with AC-600-800 (Hoffman et al, 2018), which is a consequence of the different production process and precursor of the commercial AC (precursor: peat, carbonization temperature: 500°C, physical activation).…”
Section: Influence Of Additives On Ecmentioning
confidence: 99%
“…Hence, it can be concluded that the binder content should be reduced to a minimum or that binder should even be avoided in electrode manufacturing. Liu et al already made first attempts to develop such binder-free electrodes based on banana peel (Liu et al, 2016), but this approach is relatively new and far from being able to be implemented in electrode production on an industrial scale. The higher EC values of AC-600-800-add compared to those of AC-add can be explained by the lower surface are of the commercial AC in comparison with AC-600-800 (Hoffman et al, 2018), which is a consequence of the different production process and precursor of the commercial AC (precursor: peat, carbonization temperature: 500°C, physical activation).…”
Section: Influence Of Additives On Ecmentioning
confidence: 99%
“…The peak at 285.5 eV can be assigned to the CO/CN functional groups. The peak at 288 eV is attributed to the OCO functional groups . The oxygen spectra also consisted of three peaks (Figure c).…”
Section: Resultsmentioning
confidence: 97%
“…Carbon compounds, such as graphene, carbon nanotubes, and porous carbons, have received extensive attention as electrode materials in EDLCs. Given the need for the development of cost‐effective, well‐performing electrode materials, carbon materials that have a high specific surface area and hierarchical porous structures are an efficient way of obtaining satisfactory electrochemical performance when used as the electrodes in EDLCs .…”
Section: Introductionmentioning
confidence: 99%
“…To prepare biomass-derived carbon with superior supercapacitive performance, the following criteria should be considered: (i) the precursors with intrinsic porous structures, especially interconnected meso/microporous structures are preferred; (ii) the intrinsic microporous structures are preserved as the precursors are converted to carbon during the carbonization and activation process; (iii) low KOH/C mass ratio (~1-3) and longer activation time are suggested for the activation process in the appropriate temperature range (700-900 • C). To further compare the performance of different biomass-derived carbons in supercapacitor applications and their structure-property relationship, a detailed comparative study is presented in Table 8 [122][123][124][125][126][127][128].…”
Section: Structures and Propertiesmentioning
confidence: 99%